Inverse eigenstrain analysis of residual stresses in friction stir welds - Luckhoo, H; Jun, T; Korsunsky, A (2009)
This paper presents the results of eigenstrain analysis in a friction stir welded 12mm-thick 12%Cr steel plate. The finite element models are established for inverse eigenstrain analysis for three different model cases. As the region containing the eigenstrain distribution expands, the accuracy of the residual strain reconstruction improves. If the eigenstrain is allowed to be present along the entirety of the sample, good agreement can be achieved. It is also noting that eigenstrain (permanent plastic strain) represents the consequence of numerous inelastic processes occurring during to welding. The results suggest that significant inelastic deformation of the plate takes place even at larger distances from the weld. This conclusion requires validation by independent means, experimental and/or modelling.